PERAN AUDIT INTERNAL DALAM PENERAPAN GOOD CORPORATE GOVERNANCE PADA BADAN USAHA MILIK NEGARA PROVINSI JAWA TENGAH - Nurdhiana .; Tri Bodroastuti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
The rapid economic and business development affects business actors to enhance their awareness to manage the businessby implementing Good Corporate Governance (GCG). The implementation is aimed to avoid deceitfulness that endangerscompany’s assets. GCG becomes a key of success for a company to grow and earn profit in a long term, so it can winglobal competitiveness. The implementation of GCG in BUMN is not easy. So, it needs more independent and professionalmanagement to do its tasks. The role of independent internal auditors is important in implementing GCG. The internalaudits are required to provide information on sufficiency and affectivity of company’s internal control. An internal auditormust be one who has competency in finance because his role is to watch managerial activities. Besides knowledge onauditing, an auditor is expected to have knowledge on audited substance. Therefore, the competency of internal auditorsare needed to bridge the needs of Commissioner Board on auditing roles and internal controls with constraints absorptionof technical problems in accounting, auditing, and internal control. The result of this research showed that most BUMNs inbanking sector in Central Java have implemented GCG. The internal audits are in line with Commissioner Board, if so theBoard makes mistakes, it will be easily detected.Key Word : Internal audit, Good Corporate Government